GIS-based development and visualization of ground flash density maps during the monsoon seasons in Peninsular Malaysia - Roslan, N.; Ab-Kadir, M. Z. A.; Ungku Amirulddin, U. A.; Mohd Shafri, H. Z.; Abdullah, N. (IEEE, 2023)
In this paper, a novel approach to develop ground flash density (GFD) maps based on six years of lightning flash data from 2012 to 2017 in Peninsular Malaysia. By leveraging advanced Geographical Information System (GIS) software and a detailed Peninsular Malaysia basemap, the GFD maps were developed to gain a better understanding of lightning distribution patterns and identify areas of high activity. This study has demonstrated the effectiveness of the ground flash density (GFD) mapping approach in classifying the distribution of GFD and identifying hotspot areas. The highest GFD of 12 flashes/km 2 /year was observed during the First Inter-Monsoon season (April to May), indicating a period of heightened lightning activity in Peninsular Malaysia. The GFD maps produced in this study have shown that the central region of Peninsular Malaysia is the primary hotspot of GFD for all monsoon seasons. These findings are significant for utility and protection engineers, who can utilize this information to plan and improve the reliability of power grids through effective protection systems. By minimizing power outages caused by lightning strikes, the reliability of power grids can be significantly enhanced.